2018
DOI: 10.1038/s41467-018-04735-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the regulation of human 5,10-methylenetetrahydrofolate reductase by phosphorylation and S-adenosylmethionine inhibition

Abstract: The folate and methionine cycles are crucial for biosynthesis of lipids, nucleotides and proteins, and production of the methyl donor S-adenosylmethionine (SAM). 5,10-methylenetetrahydrofolate reductase (MTHFR) represents a key regulatory connection between these cycles, generating 5-methyltetrahydrofolate for initiation of the methionine cycle, and undergoing allosteric inhibition by its end product SAM. Our 2.5 Å resolution crystal structure of human MTHFR reveals a unique architecture, appending the well-co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(163 citation statements)
references
References 52 publications
9
153
1
Order By: Relevance
“…The modeled yeast MTHFR structure aligns well with human MTHFR protein with rmsd value of 0.48 Å ( Figure S2), which exists as a homodimer with each monomer consisting of a catalytic domain and a regulatory domain ( Figure S3). The two monomers are held together by interactions of the regulatory domain, as has been reported for the human MTHFR (10).…”
Section: The Regulatory Region Of the Yeast Mthfr Protein Met13p: Prmentioning
confidence: 80%
See 2 more Smart Citations
“…The modeled yeast MTHFR structure aligns well with human MTHFR protein with rmsd value of 0.48 Å ( Figure S2), which exists as a homodimer with each monomer consisting of a catalytic domain and a regulatory domain ( Figure S3). The two monomers are held together by interactions of the regulatory domain, as has been reported for the human MTHFR (10).…”
Section: The Regulatory Region Of the Yeast Mthfr Protein Met13p: Prmentioning
confidence: 80%
“…We initially built a homology model of the yeast MTHFR, Met13p, based on the crystal structure of human MTHFR, which has been recently solved (10). The modeled yeast MTHFR structure aligns well with human MTHFR protein with rmsd value of 0.48 Å ( Figure S2), which exists as a homodimer with each monomer consisting of a catalytic domain and a regulatory domain ( Figure S3).…”
Section: The Regulatory Region Of the Yeast Mthfr Protein Met13p: Prmentioning
confidence: 99%
See 1 more Smart Citation
“…SHMT1 protein levels, by contrast, are elevated during the S phase of HeLa cells, but without changes in mRNA levels. 115,116 Meanwhile, we found that phosphorylation of MTHFR leads to an increased sensitivity to AdoMet inhibition, 117 and the kinase responsible for this phosphorylation has been suggested to be the cyclin dependent kinase 1 (CDK1) in association with cyclin B1. 118 Together, these data provide a link between the cellcycle state and regulation of proteins involved in methionine cycle or the one-carbon metabolic pathway.…”
Section: Allosteric Genetic and Epigenetic Regulationmentioning
confidence: 99%
“…The inhibition of this enzyme is helpful in the treatment of HIV infection 50 . Moreover, MTHFR having PDB ID 6FCX is concerned with the irreversible reduction of 5,10‐methylenetetrahydrofolate to 5‐methyl‐tetrahydrofolate that is indirectly involved in the biosynthesis of monophosphates and purines 51 . This target is believed to be essential for the investigation of anticancer drugs 52 …”
Section: Introductionmentioning
confidence: 99%